Polysaccharide Cryogels Containing β-Cyclodextrin for the Delivery of Cannabidiol - Denitsa Momekova; Yavor Danov; Georgi Momekov; Ervin Ivanov; Petar Petrov (MDPI AG, 2021)
Cannabidiol (CBD) has attracted increasing interest due to its therapeutic potential for treating numerous diseases. However, CBD is very lipophilic and has very unfavorable pharmacokinetics and low bioavailability. Efforts are focused on developing drug delivery systems for enhanced solubilization and therapeutic activity of CBD. Here, we report the preparation of original super-macroporous cryogels from 2-hydroxyethyl cellulose (HEC) and β-cyclodextrin (β-CD) designed for the topical delivery of CBD. The cryogels were synthesized by photochemical crosslinking in a frozen aqueous system, purified, and then loaded with CBD. The effect of HEC/β-CD mass ratio (100:0; 50:50; 40:60 and 20:80) in the reaction mixture on the reaction efficiency, physico-mechanical properties of cryogels, drug release profile, and antineoplastic potential were evaluated in detail. The cryogels showed a bi-phasic release behavior: initial burst release in the first 3 hours followed by slower drug release which can be beneficial in the treatment of cutaneous neoplastic diseases.